Management of obstetric anal sphincter injury: Colorectal surgeons' perspectives in Australia and New Zealand. (15th October 2020) - Oh, Daniel; Wright, Caroline; Young, Christopher J.
Abstract : Background: Obstetric anal sphincter injuries (OASIs) are a significant complication of vaginal delivery, and a leading cause of anal incontinence in women. Aims: The aims were to explore the management of OASIs in Australia and New Zealand (ANZ) by colorectal surgeons and how this compares with current recommendations and international experience, and to identify the deterrents to the provision of best‐practice care among colorectal surgeons. Materials and Methods: Three hundred colorectal surgeons of the Colorectal Surgical Society of ANZ were mailed questionnaires. Areas of interest included: surgeon demographics; exposure to OASIs; understanding of current recommendations; and opinions regarding the importance of symptoms and assessment tools in OASIs. Results: There were 94 completed questionnaires (response rate 31.3%). Fifty‐seven surgeons (60.6%) reported low exposure to OASIs during their fellowship training. Greater than 90% believed patients with grade three tears and above should have anal sphincter assessment. Sixty‐six (70.2%) reported that they routinely review women who have had OASIs. However, 56.4% were unaware if their obstetrics department followed a standard protocol for OASIs. Surgeons practising in metropolitan centres reported higher rates of their obstetrics department following a protocol ( P = 0.013), and greater access to investigative tools ( P < 0.001), when compared to rural‐based surgeons. Conclusions: Most ANZ colorectal surgeons have had minimal training in OASI management. Colorectal surgeons are more commonly involved with OASI patients in the non‐acute setting. Management protocols involving a multidisciplinary team of both colorectal surgeons and obstetricians should be clearly defined, and the gap between metropolitan and rural centres needs to be reviewed.